A study on various clinical presentations of extradural hemorrhage, factors affecting treatment and early outcome - Kumar, Ch. Surendra; Prasad, K. Satyavara; Rajasekhar, B.; Raman, B. V. S. (International Journal of Research in Medical Sciences, 2017)
Background: In India 11% of deaths are due to trauma and 78% of injury deaths are due to head injury. The aim of this study was to analyse the clinical spectrum and to evaluate the postoperative outcome in patients with head injury with an extradural hematoma. Methods: This was a retrospective observational study which included 100 patients admitted in King George hospital, Andhra medical college, Visakhapatnam, Andhra Pradesh, India over the past two years (01/10/2014 to 30/09/2016) with head injury, diagnosed to have traumatic extradural hemorrhage. A detailed clinical history, physical examination and CT scan was performed in all patients. For patients who were subjected to surgery operative and post-operative findings were noted. Results: The maximum patients suffering from EDH are in the age group of 21-30 years (28%) with male predominance (95%). The most common mode of injury is RTA (58%) under the influence of alcohol. Majority of cases reached hospital within 6 hours from time of injury (44%). 95% of patients with EDH presented with LOC followed by vomiting in 68% of cases, followed by Headache in 42% of cases. 53% of the cases presented with mass effect over brain parenchyma with frontal EDH as most common location. Out of 100 cases, surgical approach was considered in 57 patients while remaining 47 patients were managed conservatively. Recovery from clinical and functional morbidity was satisfactorily acceptable, following treatment. Conclusions: Early presentation with mild to moderate GCS has good clinical outcome with minimal disability.